2015
DOI: 10.1364/oe.23.018645
|View full text |Cite|
|
Sign up to set email alerts
|

Avoiding the requirement for pre-existing optical contact during picosecond laser glass-to-glass welding

Abstract: Previous reports of ultrafast laser welding of glass-to-glass have indicated that a pre-existing optical contact (or very close to) between the parts to be joined is essential. In this paper, the capability of picosecond laser welding to bridge micron-scale gaps is investigated, and successful welding, without cracking, of two glasses with a pre-existing gap of 3 µm is demonstrated. It is shown that the maximum gap that can be welded is not significantly affected by welding speeds, but is strongly dependent on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 18 publications
(25 reference statements)
1
26
0
Order By: Relevance
“…Figure 6 shows the measurement results of the surface roughness near the welding area by changing the etching time up to 40 min. According to published papers, optical contacted fused silica welding with ultrafast laser can bridge a 1 to 3 μm gap [20,35]. In conclusion, our etching time of 30 min, generating a surface roughness of 10 nm, which is still less than a hundredth of the wavelength of the welding laser, will not affect the welding efficiency [30].…”
Section: Resultsmentioning
confidence: 99%
“…Figure 6 shows the measurement results of the surface roughness near the welding area by changing the etching time up to 40 min. According to published papers, optical contacted fused silica welding with ultrafast laser can bridge a 1 to 3 μm gap [20,35]. In conclusion, our etching time of 30 min, generating a surface roughness of 10 nm, which is still less than a hundredth of the wavelength of the welding laser, will not affect the welding efficiency [30].…”
Section: Resultsmentioning
confidence: 99%
“…The laser microwelding system enables the generation of weld seams at the interface of two glass plates, as demonstrated in References [ 41 , 42 ]. Previously, however, the welds were generated in relatively small areas (typically less than 5 mm × 5 mm).…”
Section: Resultsmentioning
confidence: 99%
“…This plasma expands and locally melts a small volume of surrounding glass that crosses into the bottom part of the cover glass (glass plate #1), and, when this solidifies on cooling, it forms a weld. Our previous work [ 42 ] showed that gaps smaller than 3 µm can be closed during the laser welding process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This degradation of the sealing quality can be mitigated by using ultrafast laser welding. Prior studies showed that ultrafast laser glass welding can effectively bond glass substrates by filling the interface gap up to 3 μm [46,47]. Figure 2B provides a schematic illustration of the ultrafast laser welding of a cover glass to the sensor substrate.…”
Section: Methodsmentioning
confidence: 99%